Chronic AMR in Liver Transplant: Validation of the 1-Year cAMR Score's Ability to Determine Long-term Outcome. Issue 9 (September 2017) - O'Leary, Jacqueline G.; Smith, Cory; Cai, Juncao; Hart, Brent; Jennings, Linda W.; Everly, Matthew; Klintmalm, Goran B.; Demetris, Anthony J.
Abstract : Background: A proposed chronic antibody-mediated rejection (AMR) score has recently predicted 50%10-year death-censored allograft loss in patients with donor-specific alloantibodies (DSA) mean florescence intensity (MFI) greater than 10 000 and requires confirmation in patients with lower MFI (1000-10 000). Methods: All patients who underwent liver transplantation from January 2000 to April 2009, had DSA (MFI ≥1000) in serum 10 to 14 months postliver transplantation, and had a protocolized liver biopsy were evaluated (n = 230). The previously proposed chronic AMR (cAMR) score was used to risk-stratify putative chronic AMR in DSA+ patients with MFI from 1000 to 10 000. Results: The MFI distribution of DSA+ recipients were as follows: 66% had MFI 1000 to 4999, 14% had MFI 5000 to 10 000, and 20% had MFI greater than 10 000. The cAMR score distribution on 1-year protocol liver biopsy found that 41% had a score less than 13; 27% a score of 13 to 27.5, and 32% a score greater than 27.5. MFI correlated with 1-year cAMR category (<13, 46% vs 21% and >27.5, 29% vs 42% when MFI was 1000-10 000 vs MFI >10 000; P = 0.047). In patients with a cAMR score less than 13, 10-year death-censored allograft survival was 96% to 100% regardless of MFI ( P = NS). The risk of allograft loss increased in patients with a cAMR score greater than 13 ( P = 0.004) in DSA+ patients with MFI 1000 to 10 000. DSA MFI greater than 10 000 versus MFI 1000 to 10 000 at 1 year was also more likely to persist at 5 years (95% vs 68%; P < 0.0001). Conclusions: Validation of the previously proposed cAMR score in a separate cohort predicts death-censored long-term allograft failure in DSA+ patients regardless of MFI, and higher MFI at 1 year predicts DSA persistence at 5 years. Abstract : The authors validate the previously proposed cAMR score in a separate cohort of patients showing its predictability of death-censored long-term allograft failure in DSA+ patients regardless of MFI (MFI > 1000 vs > 10 0000). Supplemental digital content is available in the text.